Effects of Resveratrol on Vitrified Porcine Oocytes. (5th October 2013) - Giaretta, Elisa; Spinaci, Marcella; Bucci, Diego; Tamanini, Carlo; Galeati, Giovanna
Abstract : Vitrified MII porcine oocytes are characterized by reduced developmental competence, associated with the activation of the apoptotic pathway. Resveratrol (R), a polyphenolic compound present in several vegetal sources, has been reported to exert, among all its other biological effects, an antiapoptotic one. The aim of this study was to determine the effects of R (2  µ M) on the apoptotic status of porcine oocytes vitrified by Cryotop method, evaluating phosphatidylserine (PS) exteriorization and caspases activation. R was added during IVM (A); 2 h postwarming incubation (B); vitrification/warming and 2 h postwarming incubation (C); all previous phases (D). Data on PS exteriorization showed, in each treated group, a significantly higher (P < 0.05 ) percentage of live nonapoptotic oocytes as compared with CTR; moreover, the percentage of live apoptotic oocytes was significantly (P < 0.05 ) lower in all R-treated groups relative to CTR. The results on caspase activation showed a tendency to an increase of viable oocytes with inactive caspases in B, C, and D, while a significant (P < 0.05 ) increase in A compared to CTR was recorded. These data demonstrate that R supplementation in various phases of IVM and vitrification/warming procedure can modulate the apoptotic process, improving the resistance of porcine oocytes to cryopreservation-induced damage.